2023
DOI: 10.1186/s40723-023-00115-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Universal Teacher–Child Interaction Training on Hispanic teachers’ sense of self-efficacy in early childhood education and care settings

Abstract: Disparities exist in the availability of high-quality early childhood education and care settings (ECEC) across communities within the United States. Teachers have an imperative role in fostering children’s socioemotional development; however, when the classroom climate deteriorates due to disruptive behavior, meeting these emotional and learning needs becomes more difficult. Dealing with challenging behaviors can lead to emotional exhaustion which is directly linked to a decrease in teacher sense of efficacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Indeed, Management in Early Childhood Education is the study of the management of education directly related to the social sciences. (Rivas et al, 2023) demonstrated the importance of management in producing high-quality early childhood education, including by increasing teachers' sense of efficacy in classroom management, learning strategies, and child involvement.…”
Section: Figure 1 Flowchart Of Main Theme Publication Data Collectionmentioning
confidence: 99%
“…Indeed, Management in Early Childhood Education is the study of the management of education directly related to the social sciences. (Rivas et al, 2023) demonstrated the importance of management in producing high-quality early childhood education, including by increasing teachers' sense of efficacy in classroom management, learning strategies, and child involvement.…”
Section: Figure 1 Flowchart Of Main Theme Publication Data Collectionmentioning
confidence: 99%
“…Providing teachers with professional training, such as teaching training, classroom management training, training for communicating with students and colleagues, and selfpsychological adjustment training will help teachers to manage the classroom and deal with various challenges from teaching and schoolwork, thus reducing the probability of teachers suffering from burnout. Rivas et al (2023) [26] measured the changes of teachers' self-efficacy and job burnout after participating in teacher-child interactive training (TCIT) through a randomized wait-list controlled study, and the results showed that TCIT is an effective intervention. It can improve teachers' efficacy in classroom management, teaching strategies, and student engagement, and reduce burnout levels.…”
Section: Professional Training (Pt)mentioning
confidence: 99%